2016
DOI: 10.1007/s10620-016-4242-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Endoscopic Balloon Dilation for Upper Gastrointestinal Strictures of Crohn’s Disease

Abstract: EBD was a safe procedure, but not a potent therapy for Crohn's upper GI strictures. Meanwhile, 1-month response could serve as an early predictor of the long-term response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Two recent studies on dilation of de novo upper gastrointestinal strictures associated with CD showed a technical success rate of 93% and an overall complication rate of 3–4%. EBD delayed the need for surgery in about 56–66% of patients over a median follow‐up of 23 to 24 months . Similarly, emerging data from retrospective studies, revealed that double‐balloon endoscopy‐assisted EBD provided a reasonable technical success rate (72% to 100%), short‐term efficacy (about 70%), and safety (complication rate of 0% to 10%) in patients with small intestinal CD‐associated de novo strictures.…”
Section: Management Of Crohn's Disease Associated Stricturesmentioning
confidence: 98%
“…Two recent studies on dilation of de novo upper gastrointestinal strictures associated with CD showed a technical success rate of 93% and an overall complication rate of 3–4%. EBD delayed the need for surgery in about 56–66% of patients over a median follow‐up of 23 to 24 months . Similarly, emerging data from retrospective studies, revealed that double‐balloon endoscopy‐assisted EBD provided a reasonable technical success rate (72% to 100%), short‐term efficacy (about 70%), and safety (complication rate of 0% to 10%) in patients with small intestinal CD‐associated de novo strictures.…”
Section: Management Of Crohn's Disease Associated Stricturesmentioning
confidence: 98%
“…In general, there is a high rate of recurrence of obstructive symptoms, and repeated dilatations are required to treat them properly and avoid surgery[50,103]. A retrospective study by Guo et al[104] evaluated the safety and efficacy of endoscopic balloon dilations for the treatment of stenoses in 24 patients with gastroduodenal DC associated with obstructive symptoms, less than 4 cm, not associated with fistulas or abscesses. They demonstrated that the procedure was safe but had unfavorable long-term effectiveness.…”
Section: Treatmentmentioning
confidence: 99%
“…The definitions used for the explored parameters of included studies [16][17][18][19] are reported in the Supplementary Materials and Methods section and Supplementary Table 1.…”
Section: Data Collectionmentioning
confidence: 99%
“…There were 141 total dilation procedures. Seventy patients undergoing 112 dilations have been published in multiple individual smaller series previously, [16][17][18][19][20][21] and 24 patients undergoing 29 dilations were not in previously published reports but were added through our multicenter collaboration ( Table 1). The demographics of this population are shown in Table 2.…”
Section: Pooled Individual Patient Analysismentioning
confidence: 99%